Impact of Age on the Functional Evaluation of Intermediate Coronary Stenoses With Instantaneous Wave-Free Ratio and Fractional Flow Reserve. (January 2021) - Verdoia, Monica; Gioscia, Rocco; Nardin, Matteo; Negro, Federica; Tonon, Francesco; Suryapranata, Harry; Khedi, Elvin; Marcolongo, Marco; De Luca, Giuseppe
The optimal strategy for assessing the ischemic significance of intermediate coronary stenoses with adenosine-induced fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) is still debated. Few studies have previously assessed the impact of age on FFR and iFR, which was the aim of our study. Patients undergoing FFR and iFR evaluation for intermediate (40%-70%) coronary lesions were included and divided according to age. Fractional flow reserve was performed by intracoronary boluses of adenosine (60-1440 μg). Instantaneous wave-free ratio was automatically calculated. Among 148 patients undergoing FFR measurement of 166 lesions, 45.3% were ≥70 years. Elderly patients had higher minimal lumen diameter ( P = .03). We also observed a linear relationship between iFR and FFR independently of age. Fractional flow reserve values were higher in the elderly patients, whereas iFR was not related to age. A total of 33 lesions had a positive iFR with no difference for age (17.3% vs 22%, P = .56), while FFR <0.80 was more infrequent in the elderly patients (17.1% vs 34.8%, P = .02). In intermediate coronary stenoses, iFR and FFR correlation is unaffected by age. Fractional flow reserve is higher in the elderly patients, whereas iFR is less affected by age. Future large-scale studies are needed to define whether iFR should be the preferred choice in elderly patients.